Efficient and irreversible antibody–cysteine bioconjugation using carbonylacrylic reagents. Issue 1 (January 2019) - Bernardim, Barbara; Matos, Maria; Ferhati, Xhenti; Compañón, Ismael; Guerreiro, Ana; Akkapeddi, Padma; Burtoloso, Antonio; Jiménez-Osés, Gonzalo; Corzana, Francisco; Bernardes, Gonçalo
Abstract There is considerable interest in the development of chemical methods for the precise, site-selective modification of antibodies for therapeutic applications. In this protocol, we describe a strategy for the irreversible and selective modification of cysteine residues on antibodies, using functionalized carbonylacrylic reagents. This protocol is based on a thiol–Michael-type addition of native or engineered cysteine residues to carbonylacrylic reagents equipped with functional compounds such as cytotoxic drugs. This approach is a robust alternative to the conventional maleimide technique; the reaction is irreversible and uses synthetically accessible reagents. Complete conversion to the conjugates, with improved quality and homogeneity, is often achieved using a minimal excess (typically between 5 and 10 equiv.) of the carbonylacrylic reagent. Potential applications of this method cover a broad scope of cysteine-tagged antibodies in various formats (full-length IgGs, nanobodies) for the site-selective incorporation of cytotoxic drugs without loss of antigen-binding affinity. Both the synthesis of the carbonylacrylic reagent armed with a synthetic molecule of interest and the subsequent preparation of the chemically defined, homogeneous antibody conjugate can be achieved within 48 h and can be easily performed by nonspecialists. Importantly, the conjugates formed are stable in human plasma. The use of liquid chromatography–mass spectrometry (LC–MS) analysis is recommended for monitoring the progression of the bioconjugation reactions on protein and antibody substrates with accurate resolution. Site-selective modification of antibodies is useful for therapeutic and imaging applications. This protocol is an alternative to maleimide labeling in which cysteine reacts selectively and irreversibly with functionalized carbonylacrylic reagents.